The Impact of Large Class Sizes on Student Concentration in the Second Semester of Islamic Education at UIN Professor Kiai Haji Saifuddin Zuhri Purwokerto - Risa Ayu Rizki Ananti; Ellen Prima (Journal of Contemporary Pedagogy and Learning Science, 2026)
This study investigates the impact of large class size on the learning concentration of second-semester students enrolled in the Islamic Education (PAI) Program at UIN Professor Kiai Haji Saifuddin Zuhri Purwokerto. Employing a quantitative descriptive survey design, the research involved 23 students from Class 2 PAI F selected through purposive sampling. Data were collected using a structured questionnaire distributed through Google Forms and analyzed using descriptive percentage techniques. The findings indicate that large class conditions generate significant environmental and psychological challenges affecting students’ concentration. A total of 87.0% of respondents reported experiencing classroom noise distractions, while 78.2% encountered difficulties related to visibility and audibility. Environmental discomfort and fatigue were reported by 65.2% of participants, and 95.7% acknowledged frequent loss of concentration during lectures. The accumulation of these conditions contributed to reduced comprehension of course materials, as indicated by 69.6% of respondents. The study demonstrates that learning concentration is influenced by the interaction of physical, environmental, and instructional factors within large-class settings. These findings highlight the importance of optimizing class capacity to support effective learning, sustained attention, and instructional quality in higher education environments